1998
DOI: 10.1016/s0893-133x(98)00064-5
|View full text |Cite
|
Sign up to set email alerts
|

Mood and Performance Changes in Women with Premenstrual Dysphoric Disorder Acute Effects of Alprazolam

Abstract: This study determined if women with premenstrual dysphoric disorder (PMS) showed impaired mood and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 47 publications
4
41
1
Order By: Relevance
“…Since there is no evidence that PMDD women differ in the density or affinity of peripheral benzodiazepine receptors, at least as measured on lymphocytes (Daly et al, 2001), the findings of Sundstrom and colleagues indicate diminished functional sensitivity of GABA A receptors in PMDD. This is consistent with studies finding modest or no clinical efficacy with benzodiazepine treatment for PMDD (Schmidt et al, 1993;Freeman et al, 1995;Evans et al, 1998), though exceptions exist (Harrison et al, 1987), and with lack of clinical benefit associated with a progesterone intervention or with progesterone induction of supraphysiologic levels of 5α-and 5β-progesterone metabolites Vanselow et al, 1996;see Wyatt et al, 2001 for review). It is also consistent with the results of a placebo-controlled clinical trial of antidepressants that found that PMDD women who were classified as "improved" with treatment had significantly lower, and not higher, plasma allopregnanolone concentrations at post-treatment than PMDD women who did not improve (Freeman et al, 2002).…”
Section: Hpa Axis and Gaba A Receptor Function In Pmddsupporting
confidence: 72%
“…Since there is no evidence that PMDD women differ in the density or affinity of peripheral benzodiazepine receptors, at least as measured on lymphocytes (Daly et al, 2001), the findings of Sundstrom and colleagues indicate diminished functional sensitivity of GABA A receptors in PMDD. This is consistent with studies finding modest or no clinical efficacy with benzodiazepine treatment for PMDD (Schmidt et al, 1993;Freeman et al, 1995;Evans et al, 1998), though exceptions exist (Harrison et al, 1987), and with lack of clinical benefit associated with a progesterone intervention or with progesterone induction of supraphysiologic levels of 5α-and 5β-progesterone metabolites Vanselow et al, 1996;see Wyatt et al, 2001 for review). It is also consistent with the results of a placebo-controlled clinical trial of antidepressants that found that PMDD women who were classified as "improved" with treatment had significantly lower, and not higher, plasma allopregnanolone concentrations at post-treatment than PMDD women who did not improve (Freeman et al, 2002).…”
Section: Hpa Axis and Gaba A Receptor Function In Pmddsupporting
confidence: 72%
“…These dramatic cyclical changes in mood in women with PMDD have been well documented both clinically and in research studies (e.g. De Ronchi et al, 2005;Evans et al, 1998;Freeman et al 1985;Halbreich et al 1982;Landen et al, 2007;Rapkin et al 1989). …”
Section: Introductionmentioning
confidence: 84%
“…Another study (Morgan and Rapkin, 2002) that also assessed a full series of neurocognitive tasks reported no performance differences between women with PMDD and control women, despite a relatively large sample size. In a previous study conducted in our laboratory (Evans et al, 1998), we assessed changes in mood and performance as a function of menstrual cycle phase in women with confirmed PMDD after placebo or alprazolam administration. When placebo was administered, motor coordination (via a balance task) and performance on the Digit Symbol Substitution Task (DSST) were impaired in the luteal phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess delayed free recall, participants repeated this task 210 min later. This was followed by a recognition test, in which participants had to identify the 12 words shown earlier from a list containing 48 words (Evans et al, 1998).…”
Section: Methods Study 1: Marijuana Smokersmentioning
confidence: 99%